Pengaruh Perbandingan Rasio Tandan Kosong Sawit (TKS) Dan Lumpur IPAL Minyak Sawit Terhadap Nilai Kalor Briket - Abdil Aziz Al Hakim; Elvi Yenie; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Energy needs at this time still depend on fossil fuels that can not be renewed, therefore we need alternative fuels that are renewable, environmentally friendly and economical, one of which is briquettes. Variations in the variables used were composition of waste oil palm empty fruit bunches and oil palm sludge, namely 90%: 10%, 80%: 20%, 70%: 30%, and 60%: 40%. The results showed that the best heating value of briquettes and compressive strength of briquettes were found in the composition of raw materials 90%: 10% with the heating value of 5098.82 cal / gr.Keywords: briquettes, oil palm empty fruit bunches, palm oil WWTP sludge.